If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10b + 10 + 2b = -10 + 8b Reorder the terms: 10 + 10b + 2b = -10 + 8b Combine like terms: 10b + 2b = 12b 10 + 12b = -10 + 8b Solving 10 + 12b = -10 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. 10 + 12b + -8b = -10 + 8b + -8b Combine like terms: 12b + -8b = 4b 10 + 4b = -10 + 8b + -8b Combine like terms: 8b + -8b = 0 10 + 4b = -10 + 0 10 + 4b = -10 Add '-10' to each side of the equation. 10 + -10 + 4b = -10 + -10 Combine like terms: 10 + -10 = 0 0 + 4b = -10 + -10 4b = -10 + -10 Combine like terms: -10 + -10 = -20 4b = -20 Divide each side by '4'. b = -5 Simplifying b = -5
| -6x-x=20 | | 19x-(8x-4)=92 | | (X+78)x+41=95 | | -2=b-11 | | 126=-7(-5a-3) | | 3(x+2)=2(2+x) | | 2(-6-5x)=68 | | 5x+6-x=7+5x-6 | | (X+78)x+42=95 | | 3x+7y=62 | | 3(x+40)= | | (5x-4)(5x+4)=80 | | b-4+2b=27 | | 5-3x=10x-35+2 | | -7(c+372)+620=-185 | | 4(5z+1)-6=178 | | 2(n+7)=5n+8 | | b-4+26=27 | | (X+41)x+78=95 | | 53=29-4(x-4) | | (X+41)+x+78=95 | | 7+2[m-4]=3 | | 90=(3x+13)(5x-7) | | 20%*5000= | | (3x^2+7x-4)+(2x^2-3x-9)= | | 5-9n=31 | | 3h+2h+9=54 | | 13=5x+1-3x | | .20*5000= | | 2975+X(175.75)=5962.72 | | 9+-5x=12+-1(6x+7) | | 0.3(4x-2)=-0.8x+9.4 |